Myoblast-derived exosomal Prrx2 attenuates osteoporosis via transcriptional regulation of lncRNA-MIR22HG to activate Hippo pathway - Yunchao Li; Xiaoxiao Wang; Changyu Pan; Hui Yuan; Xinyi Li; Zejun Chen; Haoyu He (BMC, 2023)
Abstract Background Sarcopenia and osteoporosis are common diseases that predominantly affect older individuals. The interaction between muscle and skeleton exerts pivotal roles in bone remodeling. This study aimed to explore the function of myoblast-derived exosomal Prrx2 in osteogenic differentiation and its potential mechanisms. Methods Exosomes were isolated from myogenic differentiated C2C12 cells. qRT-PCR and Western blotting were used to determine target molecule expression. Osteogenic differentiation of BMSCs was evaluated by Alizarin red staining, ALP activity and levels of OCN, OPN, RUNX2, and BMP2. Dual-luciferase reporter assay, RIP, and ChIP assays were performed to verify the interaction between molecules. The nuclear translocation of YAP1 was observed by immunofluorescence staining. In vivo osteoporotic model was established by ovariectomy in mice. Bone loss was examined using HE staining. Results Prrx2 expression was elevated in myogenic differentiated C2C12 cells and their exosomes. Myoblast-derived exosomal Prrx2 enhanced osteogenic differentiation of BMSCs. Delivering exosomal Prrx2 directly bond to MIR22HG promoter and promoted its transcription and expression. MIR22HG enhanced expression and nuclear translocation of YAP via sponging miR-128, thus facilitating BMSC osteogenic differentiation. Knockdown of exosomal Prrx2 suppressed osteogenic differentiation, which could be abolished by MIR22HG overexpression. Similarly, miR-128 inhibitor or YAP overexpression reversed the inhibitory effect of MIR22HG depletion or miR-128 mimics on osteogenic differentiation. Finally, myoblast-derived exosomal Prrx2 alleviated osteoporosis in mice via up-regulating MIR22HG and activating the Hippo pathway. Conclusion Myoblast-derived exosomal Prrx2 contributes to transcriptional activation of MIR22HG to activate YAP pathway via sponging miR-128, thereby facilitating osteogenic differentiation of BMSCs.